Iodine Deficiency Disorder Control Programme Impact in Pregnant Women and Status of Universal Salt Iodization - AK Sinha; S Tripathi; NK Gandhi (Tehran University of Medical Sciences, 2011)
Background: Several studies pertaining to current status of Iodine Deficiency Disorder Control Programme in India have revealed goiter prevalence in the range of 1.5- 44.5%, mean urinary iodine excretion level ranging from 92.5-160 mcg/L and iodized salt coverage ranging from 37-62.3%. Most of these studies were based on school children. However, very few studies have focused on pregnant women. This population is very sensitive to marginalized iodine deficiency throughout their gestational period. Methods: This 40 cluster cross sectional study was done in Raipur district. Iodine content of salt was estimated by using "Rapid Salt Testing Kits" along with observing salt storage practices, at household and in shops. Pregnant women were interviewed by using semi structured comprehensive questionnaire, which was based on knowledge attitude, and practices about salt use pattern and awareness about IDDCP, UIE level were also estimated. Results: Prevalence of goiter was 0.17%. Many (41.12%) pregnant women had <15ppm iodine content in the salt sample and 51.58% of women had subnormal iodine uptake. Wrong salt storage practice was observed in 36.3% of households.Conclusions: There were lacunae in Iodine deficiency control program in Chhattisgarh. Implementation and monitoring of program was weak. Thus for monitoring purpose IDD Cell & IDD Laboratory should be established at district level. This will lead to periodic assessment of Iodine Deficiency Disorders, by monitoring of Iodine intake and all other preventive, promotive as well as curative measures in the state.